Efecto de las estrategias de gestión de riesgos en la selección de proveedores en la Autoridad para el Desarrollo de la Cuenca Inferior del Río Benue, Makurdi, Nigeria - Tyozenda, Aondofa (2025)
This study examined the impact of risk management strategies on supplier selection at the Lower Benue River Basin Development Authority (LBRBDA) in Makurdi. It was motivated by the growing importance of effective supplier selection in public procurement and the need to assess how organizations manage procurement-related risks. The research specifically examined the effects of risk avoidance, risk mitigation, and risk transfer on the supplier selection process. A cross-sectional survey design was employed, utilizing a census approach to cover the entire population of 101 staff members. From the questionnaires distributed, 86 were returned, representing an 85.1% response rate, considered statistically reliable. Data were gathered using structured questionnaires and analyzed using descriptive and inferential statistics, particularly multiple regression. Results indicated that each strategy had a significant positive effect on supplier selection: risk avoidance (β = 0.415, p = 0.000), risk mitigation (β = 0.476, p = 0.000), and risk transfer (β = 0.365, p = 0.001). The study concludes that adopting comprehensive risk management strategies significantly improves supplier selection in public sector procurement. The study recommends institutionalizing structured risk mitigation and avoidance into procurement planning, while strategically applying risk-transfer mechanisms to strengthen supplier reliability and resilience.